Code and pattern: Algorithms enhancing design projects - Graciano, Andréa (2021)
The objective of this work is to present, through practical experiments, the possibilities of using algorithms (computational or not) in a pattern design project, in order to enhance its results. For this to occur, the project must be thought of in terms of what can be “programmed”, appropriating concepts such as module, parameterization and randomness. This article presents a pattern construction approach based on its 4 dimensions: elements, colors, structure and composition. It is proposed to insert the parametric design in the element development stage, noting that as the number of defined parameters increases, so does the algorithm’s degree of freedom, resulting in a greater number of possible solutions for the project. In the composition phase, the generative design is applied through a computational algorithm that allows the random permutation of visual modules on a given structure, creating several options for the final pattern.